Prediction of placenta accreta spectrum in placenta previa surgery using systemic inflammatory markers - Beyazıt, Ahmet; Dolapçıoğlu, Kenan Serdar; Soylu Karapınar, Oya; Kara, Bircan; Sevindik, Hasan Cem (The European Research Journal, 2025)
Objectives: Despite advancements in medical science, existing methodologies for predicting placental invasion in patients with previa remain insufficient. Systemic inflammatory markers have emerged as potential prognostic indicators in oncology. This study aims to explore whether systemic inflammatory parameters can predict placenta accreta spectrum (PAS) in patients with previa, given the analogous mechanisms between PAS and cancer cell invasion. Methods: This retrospective case-control study encompassed patients diagnosed with placenta previa who underwent cesarean section procedures between 2010 and 2024. The case group (PAS+) comprised patients who underwent hysterectomy, segmental resection (with histopathologically confirmed PAS), or had in situ placenta. Conversely, the control group (PAS-) included other patients. The systemic immune-inflammatory index (SII), platelet-to-lymphocyte ratio (PLR), and neutrophil-to-lymphocyte ratio (NLR) were calculated from the most recent preoperative complete blood count. A comparative analysis of demographic data, clinical findings, and systemic inflammatory markers was conducted between the groups. Results: A total of 487 patients were analyzed, with 146 (30%) classified as PAS (+) and 341 (70%) as PAS (-). The PAS (+) group exhibited significantly higher values in terms of age, gravidity, parity, and the number of prior cesarean sections (P=0.004, P